Cerebrospinal fluid dynamics at the lumbosacral level in patients with spinal stenosis: A pilot study. Issue 1 (1st November 2016) - Chun, Se‐Woong; Lee, Hack‐Jin; Nam, Koong‐Ho; Sohn, Chul‐Ho; Kim, Kwang Dong; Jeong, Eun‐Jin; Chung, Sun G.; Kim, Keewon; Kim, Dong‐Joo
ABSTRACT: Spinal stenosis is a common degenerative condition. However, how neurogenic claudication develops has not been clearly elucidated. Moreover, cerebrospinal fluid physiology at the lumbosacral level has not received adequate attention. This study was conducted to compare cerebrospinal fluid hydrodynamics at the lumbosacral spinal level between patients with spinal stenosis and healthy controls. Twelve subjects (four patients and eight healthy controls; 25–77 years old; seven males) underwent phase‐contrast magnetic resonance imaging to quantify cerebrospinal fluid dynamics. The cerebrospinal fluid flow velocities were measured at the L2 and S1 levels. All subjects were evaluated at rest and after walking (to provoke neurogenic claudication in the patients). The caudal peak flow velocity in the sacral spine (−0.25 ± 0.28 cm/s) was attenuated compared to that in the lumbar spine (−0.93 ± 0.46 cm/s) in both patients and controls. The lumbar caudal peak flow velocity was slower in patients (−0.65 ± 0.22 cm/s) than controls (−1.07 ± 0.49 cm/s) and this difference became more pronounced after walking (−0.66 ± 0.37 cm/s in patients, −1.35 ± 0.52 cm/s in controls; p  = 0.028). The sacral cerebrospinal fluid flow after walking was barely detectable in patients (caudal peak flow velocity: −0.09 ± 0.03 cm/s). Cerebrospinal fluid dynamics in the lumbosacral spine were more attenuated in patients with spinal stenosis than healthy controls. After walking, the patients experiencing claudication did not exhibit an increase in the cerebrospinal fluid flow rate as the controls did. Altered cerebrospinal fluid dynamics may partially explain the pathophysiology of spinal stenosis. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:104–112, 2017. Abstract : Phase‐contrast MR imaging enables the quantification of CSF flow. Compared with healthy controls, patients with spinal stenosis exhibit significantly attenuated CSF flow at the lumbosacral spine level, and this difference becomes more evident after walking. Disturbances in CSF hydrodynamics may contribute to the pathophysiology of neurogenic claudication in spinal stenosis.